DIGITAL TECHNOLOGY THAT ENHANCES LIFE QUALITY OF THE ELDERLY IN SAENSUK SUBDISTRICT, MUEANG DISTRICT, CHONBURI PROVINCE - Piamyoosuk, Tuanglab; Sreshthaputra, Kamolchanok (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the factors influencing the use of senior medical transportation services in Saensuk Municipality, Mueang District, Chonburi Province, with the aim of developing effective marketing strategies to meet the needs of the elderly. Method: A mixed-method research design employing an explanatory sequential approach was utilized, beginning with quantitative surveys followed by in-depth qualitative interviews to elaborate on the initial findings. Results: The study identified that digital tools enhance elderly access to healthcare, social interaction, and essential services, although barriers such as low digital literacy, high costs, and usability challenges persist. Digital communication platforms were found to significantly improve the well-being of elderly users by reducing loneliness and facilitating healthcare access. Novelty: This research offers a localized and comprehensive perspective on digital adoption among the elderly in a Thai community, suggesting practical strategies such as implementing digital literacy programs and senior-friendly technologies. It contributes to bridging the gap between technology and elderly care services, offering valuable insights for policy development and service improvement.